Metal-free benzannulation of 1, 7-diynes towards unexpected 1-aroyl-2-naphthaldehydes and their application in fused aza-heterocyclic synthesis. Issue 23 (7th March 2017) - Wang, Ai-Fang; Zhou, Peng; Zhu, Yi-Long; Hao, Wen-Juan; Li, Guigen; Tu, Shu-Jiang; Jiang, Bo
Abstract : A novel I2 -mediated benzannulation of 1, 7-diyne-involved 1, 4-oxo-migration was established, providing unexpected 1-aroyl-2-naphthaldehydes. The resulting 1-aroyl-2-naphthaldehydes were successfully applied in the synthesis of polycyclic isoindoles. Abstract : A novel I2 -mediated benzannulation of 1, 7-diyne-involved 1, 4-oxo-migration was established, providing a range of unexpected 1-aroyl-2-naphthaldehydes with a 1, 4-dicarbonyl unit. The resulting 1-aroyl-2-naphthaldehydes were successfully applied in the synthesis of benzo[ e ]isoindol-3-ones and benzo[ e ]benzo[4, 5]imidazo[2, 1- a ]isoindoles using aromatic amines and benzene-1, 2-diamines as nucleophiles, respectively. The mechanisms for the formation of these compounds were proposed.